2015
DOI: 10.1111/jan.12768
|View full text |Cite
|
Sign up to set email alerts
|

A family‐focused intervention for heart failure self‐care: conceptual underpinnings of a culturally appropriate intervention

Abstract: As the burden of chronic diseases increases globally, particularly in emerging economies, developing models of intervention that are appropriate to both the individual and the socio-cultural context are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 80 publications
0
17
0
3
Order By: Relevance
“…In these situations, patients may not feel responsible or adequate to make decisions about self-care. Although the majority of studies is reported from westernized countries, an increasing number of studies examine culturally specific education programs such as those recently reported from Thailand, Japan, and Lebanon [24–26]. …”
Section: Cultural Beliefs and Valuesmentioning
confidence: 99%
“…In these situations, patients may not feel responsible or adequate to make decisions about self-care. Although the majority of studies is reported from westernized countries, an increasing number of studies examine culturally specific education programs such as those recently reported from Thailand, Japan, and Lebanon [24–26]. …”
Section: Cultural Beliefs and Valuesmentioning
confidence: 99%
“…Varios estudios de autores como Hwang 2 , Dunbar 3 , Deek 4 , han evidenciado la asociación entre el apoyo del cuidador familiar y la mejoría en la adherencia al tratamiento; por otro lado destacan que el cuidador se convierte en uno de los actores capaz de brindar apoyo social para alcanzar conductas de autocuidado y de esta manera se puede disminuir significativamente el número de reingresos derivados por descompensaciones de su enfermedad por una inadecuada adherencia y déficit de autocuidado;…”
Section: Introductionunclassified
“…This choice is always preferred to someone coming “from the outside.” 21 Therefore, this strong family foundation can be used to begin a discussion of EOL issues. 25 Overall, 80% of African Americans consider themselves to be religious and to always seek spiritual guidance. A survey of African Americans revealed that 70% attend religious services at least a few times a month, 80% pray nearly every day, 27% read religious books, and 21% watch or listen to religious programming on television or radio daily.…”
Section: Synthesis Of the Literature And Preliminary Studiesmentioning
confidence: 99%
“…12 These themes are aligned with literature addressing the cultural challenges among African Americans. 25 …”
Section: Synthesis Of the Literature And Preliminary Studiesmentioning
confidence: 99%